Analysis Mapping of Long Dry With Drone Type Dji Spark in Hargowilis, Kokap, Kulonprogo - Indreswari Suroso; Hendriana Helda Pratama (Politeknik Negeri Batam, 2020)
This research was conducted in the village of Hargowilis, Kokap District, Kulon Progo Regency with a temperature of 31oC, with a wind speed of 13 km/h, 55% air humidity, and a height of 35 m from the ground surface. This research was carried out on November 8, 2019 with hot weather conditions and wind speeds of around 13 km/hour. The purpose of this study is to map the drought area in Mount Menoreh Hargowilis Village, Kokap, Kulon Progo. The method used in this study are preparation for making a drone, survey of area Menoreh hills in Hargowilis, Kokap, Kulon Progo planning testing at certain altitude in the air; calibration drone; taking aerial photograph in area long dry and then analysis of data then mapping the area in Hargowilis, Kokap, Kulon Progo. Calibration drone DJI Spark is the way to calibrate the drone is automatically. When the drone is turned on it automatically calibrates the accelerometer; gyrometer; and GPS Drones use rotors for propulsion and control. Rotating rotors push air down, to be able to fly forward, it requires a push from the rotor. When the rotor presses air, air pushes the rotor. Lift force to control the force up and down. The faster the rotor rotates, the greater the lift. Multicopter has the advantage of being stable against wind speed. The battery capacity of drone is 2200 mAH with camera DJI Spark. Drone time used in this study ranges from 15 minutes at a speed of 30 mph. Aerial photo results show that the Hargowilis area, Kokap, Kulon Progo Regency experienced a drought so that the Menoreh Hills became a deforested forest. Keywords: Drone, Long Dry, Mapping, Photography, Kokap